Relationship between Prayer Intensity and Anxiety Levels among Medical Students at Muslim Indonesian University - Sakti, Muhammad Reyhan; Abdullah, Rezky Putri Indrawati; Wello, Eny Arlini; Mukhtar, Shulhana; Syamsu, Rachmat Faisal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
In the dynamic environment of Indonesian universities, students, particularly those in the medical field, face a crucial juncture of personal growth amid academic rigor. This transition from youth to adulthood brings with it not only academic challenges but also psychological hurdles, notably anxiety. While anxiety is a common human experience, it can impede a student's ability to thrive. However, within the context of Indonesian culture, prayer serves as a powerful tool for mental well-being. Studies have indicated its potential to alleviate anxiety and foster a sense of calmness. Thus, this research endeavors to explore the relationship between prayer intensity and anxiety levels among the 2021 cohort of medical students at the Muslim University of Indonesia, shedding light on the intersection of spirituality and mental health in academic settings. The study revealed that the majority of the 2021 cohort of medical students at Muslim University of Indonesia are 21 years old (54.8%), predominantly female (76.7%), with most exhibiting good prayer intensity (49.3%) and normal anxiety levels (74%). Additionally, Chi-Square analysis indicated a significant relationship between prayer intensity and anxiety levels among these students (p = 0.005<0.05). The study findings indicate that the sampled 2021 medical students at Muslim University of Indonesia exhibit good prayer intensity and normal anxiety levels. Moreover, there's a significant relationship between prayer intensity and anxiety levels among these students.